Dampak Tindak Pidana Pungli terhadap Perekonomian dan Investasi di Indonesia - Alfaridzi, Muhammad; Agustin, Nenty; Susanto, Aldo Permana Putra; Hosnah, Asmak UI (AHKAM, 2023)
The purpose of this study is to explain that extortion (illegal levies) is the imposition of fees in places that should not be charged or collected. Extortion itself (illegal levies) is also often equated with extortion, fraud, or corruption. This is the impact of criminal acts in the Criminal Code rules. Extortion (illegal levies) itself is not clearly contained in the Criminal 2 Code, but illegal levies are the same as included in the criminal acts of fraud, extortion, and corruption that have been regulated in the Criminal Code. This research method uses library research (Library Research). Extortion (illegal levies) has a major impact on the economy and investment in Indonesia by having a negative impact on people who have a direct interest in public services. Extortion (illegal levies) has several causative factors such as cultural factors and organizational culture. Efforts to deal with extortion (illegal levies) are by means of repressive measures in the form of investigations into eradicating extortion in terms of its object, namely from the law itself.